The function of collective process: an analysis from the perspectives of the dogmatic general fundamental right of the process (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
Abstract: In the universe of procedural science, when studying the normative unity of the fundamental right of due process, it was found that the theories bring distinct arguments about its function. Thus, considering the treatment of collective conflicts in society, the problematization arose: what is the function of the collective process: guarantor or instrumentalist? For the confirmation or refutation of hypotheses, in a first moment, it is necessary to start with the dogmatic of fundamental rights, to present, in dialectic, the perspective of subjective rights and the perspective of objective elements; in a second moment, develop the fundamental right of due process, now reflecting the process as an instrument of the State for the realization of substantive rights of the Constitution, according to instrumentalist theories; The process as a fundamental guarantee of first dimension, in order to prevent interventions without due constitutional justification, according to institutionalist theories; which will allow, in a third moment, to broaden the focus on the collective process, By pointing the concrete problems through the lens of dogmatics, with the intention of empirical verification of their real function. Therefore, from the premises of the double perspective of the dogmatic fundamental rights and the fundamental right of legal process, the conclusion will reveal not only the function of the collective process, but also some propositions to its improvement. In the record, the article is guided by the hypothetical-deductive method and it is structured in books, scientific articles, theses, legislation and jurisprudence.